Colocasia esculenta (L.) Schott (Wild Taro): Calcium Oxalate Crystals in Leaf and Petiole Using Light Microscopy, Scanning Electron Microscopy and Energy Dispersive X-ray Spectroscopy - Paopun, Yupadee; Thanomchat, Piyanan; Kronburee, Nustsaba (Microscopy and Microanalysis Research – The Journal of The Microscopy Society of Thailand, 2024)
Calcium oxalate (CaOX) is commonly found in Thai herbs and in wild taro. CaOX is claimed to be a cause of kidney stones in humans who consume plants that contain CaOX. The aim of this study was to investigate the presence of CaOX crystals in leaf and petiole parts of C. esculenta using a light microscope, a scanning electron microscope and an energy-dispersive X-ray spectrometer. Various shapes of CaOX crystal were found, including needle-like (raphide), druse, hexagonal and octahedron. They occur in the leaf blade, midrib and petiole. In terms of size, the needle-like crystals were 45-62.5 µm long and 1.42-2 µm wide. The druses were 4.01-65.10 µm in diameter. In comparison, the hexagonal crystals were 2.71-33.80 µm long and 1.01-6.61 µm wide. The octagonal crystals were 1.8-7.38 µm long and 1.92-10.50 wide. The needle crystals formed raphide clusters in the cells while hexagonal and orthorhombic crystals were individually present in the cells. Energy dispersive X-ray spectra and X-ray maps showed that the crystals consisted of calcium (Ca) and oxygen (O). The results of this study are preliminary data that could be used in the medical field and human health care.